1D, 2D, and 3D Seismic Response Analysis of Shallow and Deep Foundation Resting on Stratified Soil Deposit - Ram A.K.; Verma A.; Mohanty S. (My University, 2025)
In the present investigation, an effort has been made to evaluate the seismic response of shallow and deep foundations resting on stratified soil-ash deposits. The stratified soil deposit has been analysed considering one-dimensional, two-dimensional, and three-dimensional domains using finite element (FE) analysis methods. The nonlinear response analysis of stratified soil-ash deposit has been performed using Cyclic1D software. The response analysis of the shallow and deep foundation resting on stratified soil-ash deposit has been carried out by employing CyclicTP and OpenSeesPL software, respectively, under seismic excitations. The Nepal earthquake (Mw: 7.8) and Uttarkashi earthquake (Mw: 6.5) have been considered as seismic input motion for all the analysis. A stratified soil-ash deposit of 20 m depth has been considered for all the analysis, which is divided into four equal layers. The acceleration, displacement, excess pore water pressure, and excess pore water pressure ratio responses are the key outcome of this study. The results of the present study may be useful for seismic design of the shallow and deep foundation resting on stratified soil-ash deposits in earthquake-prone regions. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.